1997
DOI: 10.1088/0953-4075/30/4/020
|View full text |Cite
|
Sign up to set email alerts
|

State- and isotope-dependent charge transfer of with atomic hydrogen in astrophysical and fusion plasmas

Abstract: State-and target-isotope-dependent cross sections for electron capture in collisions of N 4+ (2s) with H(1s), D(1s), and T(1s) are presented for the energy range 0.01-6000 eV amu −1 . Results are given for capture via radial coupling into the N 3+ 2s3s 1 S, 2s3p 1 P o , 2s3d 1 D, 2s3s 3 S, 2s3p 3 P o , 2s3d 3 D, and 2p3s 3 P o states and are obtained through a close-coupled, quantummechanical, molecular-orbital method. Fully ab initio molecular data determined with the spincoupled valence-bond method are incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…In this case, we still observe wider peaks in the partial cross section for T than for H, but the magnitude of the peaks is much smaller for the heavier isotope at low energy, resulting in a decrease of the cross section. This behavior of the partial cross sections has been observed in other systems such as N 4+ + H [7] or Si 4+ + He [24]. Finally, we computed the cross section with and without the rotational couplings in order to estimate their effect, and found the effect to be negligible.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In this case, we still observe wider peaks in the partial cross section for T than for H, but the magnitude of the peaks is much smaller for the heavier isotope at low energy, resulting in a decrease of the cross section. This behavior of the partial cross sections has been observed in other systems such as N 4+ + H [7] or Si 4+ + He [24]. Finally, we computed the cross section with and without the rotational couplings in order to estimate their effect, and found the effect to be negligible.…”
supporting
confidence: 68%
“…These authors interpreted this effect with the Landau-Zener-Stueckelberg model and suggested that it could occur at energies as high as 1 keV/amu for some systems. Moreover, it was established that the cross section decreases with increasing system reduced mass [7], a behavior that has since been observed in other charge-transfer collisions [8,9]. Recently, Stolterfoht et al [10,11] observed a very important isotope effect in collisions between He 2+ and H, the replacement of H by D or T leading to a variation of the cross section for energies as high as 300 eV/amu.…”
Section: Introductionmentioning
confidence: 74%
“…Nonstatistical triplet ratios have been measured in charge exchange between N 4+ and H or H 2 [31]. Those measurements are in agreement with the fully quantal closecoupled molecular orbital calculations of Stancil et al [32]. However, in the case of our measurement it is significant that captures involving two closely neighboring ion species do not follow the same trend.…”
supporting
confidence: 91%
“…These spectra are somewhat more complicated than H-like spectra because the spins of the two electrons in He-like ions couple to yield either a singlet (S = 0) or triplet (S = 1) state. A 1:3 probability ratio is usually assumed based on the statistical weight of the levels, but statistical weights have been shown to be incorrect for some circumstances both experimentally and in detailed theoretical calculations [100,131] for Be-like ions, which also have S = 0 and S = 1 states. Figures 19 and 20 show schematic energy level diagrams for electron capture into n = 4 singlet and triplet states, respectively, assuming a uniform distribution of angular momentum states for illustrative purposes.…”
Section: He-like Spectramentioning
confidence: 99%